The Antibacterial Properties of Plant-Derived Natural Colorants: A Review - Shipra Gupta (Colorants, 2025)
The world has recently witnessed the dire consequences of microbial infections in the form of the spread of COVID 19. Like viruses, bacterial infections too are a serious global health concern, especially because of the evolution of multidrug-resistant (MDR) bacterial populations. MDR bacteria are a result of the mindless use and misuse of antibiotics all over the world. Hence, there arises a need to find alternative strategies to effectively combat bacterial infections; all the more so for MDR bacterial infections. A lot of research has been conducted to find alternative antibacterial strategies such as phage therapy, the synthesis of antimicrobial peptides, the development of CRISPR-Cas systems, the incorporation of pro- and pre-biotics into our food or as supplements, and the development of bactericidal nanotechnology and antibacterial materials. Of these many strategies, this review focusses on the last one—the development of antibacterial materials. This article explores the potential of plant-derived natural colorants to serve as effective antibiotic materials to be used in various industries ranging from food, textile, paper, and leather to the pharmaceutical industry. Some major advantages of developing plant-derived natural colorants into antibacterial materials is that many of them possess inherent medicinal properties, they are biocompatible, non-toxic for humans, and biodegradable, and hence environment friendly. Many plant-derived natural colorants, like curcumin, indigo, lawsone, emodin, etc., have already been well studied for their antimicrobial properties. This review article aims at integrating some relevant studies to offer a cohesive overview of the current state of knowledge on the antibacterial properties of plant-derived natural colorants.